Is Galactose a Hormetic Sugar? An Exploratory Study of the Rat Hippocampal Redox Regulatory Network. Issue 21 (9th September 2021) - Homolak, Jan; Babic Perhoc, Ana; Knezovic, Ana; Kodvanj, Ivan; Virag, Davor; Osmanovic Barilar, Jelena; Riederer, Peter; Salkovic‐Petrisic, Melita
Abstract : Scope: Galactose, a ubiquitous monosaccharide with incompletely understood physiology is often exploited for inducing oxidative‐stress mediated aging in animals. Recent research demonstrates that galactose can conserve cellular function during periods of starvation and prevent/alleviate cognitive deficits in a rat model of sporadic Alzheimer's disease. The present aim is to examine the acute effects of oral galactose on the redox regulatory network (RRN). Methods and Results: Rat plasma and hippocampal RRNs are analyzed upon acute orogastric gavage of galactose (200 mg kg ‒1 ). No systemic RRN disbalance is observed; however, a mild pro‐oxidative shift accompanied by a paradoxical increment in tissue reductive capacity suggesting overcompensation of endogenous antioxidant systems is observed in the hippocampus. Galactose‐induced increment of reductive capacity is accompanied by inflation of the hippocampal pool of nicotinamide adenine dinucleotide phosphates indicating ROS detoxification through disinhibition of the oxidative pentose phosphate pathway flux, reduced neuronal activity, and upregulation of Leloir pathway gatekeeper enzyme galactokinase‐1. Conclusion: Based on the observed findings, and in the context of previous work on galactose, a hormetic hypothesis of galactose is proposed suggesting that the protective effects may be inseparable from its pro‐oxidative action at the biochemical level. Abstract : In contrast to parenteral administration of galactose that stimulates oxidative stress‐mediated aging in rodents, peroral gavage provides beneficial health effects. In the search for a possible mechanistic explanation, the acute effects on the hippocampal redox regulatory network reveal oral galactose might exerts its effects by hormesis.